Reagan and the States. - Nathan, Richard P. (Princeton legacy library., 2014)
Here is the most thorough study to date on the impact of Ronald Reagan's policies on the states, especially the outcomes of his well-known budget cuts. A treasure trove of information that will be essential for interpretations of the Reagan presidency. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in dur.